INFORMATION SYSTEM OF SOFTWARE DISTRIBUTION (Journal of Information Technologies in Education (ITE), 2011)
One of the approaches to building a software distribution information system is examined. The results of researches on conceptual, architectural and technological issues of software support are shown. Business, user’s and functional requirements to the software updating systems are considered. Updating system architecture is examined in whole and in particular parts. Interaction of main components of the system is revealed. The aspects of users’ feedback organisation are considered as well
Keywords: application store; distribution; e-shop; feedback; Information system; software; updates; web-service